Perceived Oral Health Status, Unmet Needs, and Barriers to Dental Care Among HIWAIDS Patients in a North Carolina Cohort: Impacts of Race - Lauren L. Patton, DDS; Ronald P. Strauss, DMD, PhD; Rosemary G. McKaig, MPH, PhD (Blackwell Synergy, 2003)
This prospective observational study examined differences in perceived oral health status, treatment needs, dental care utilization patterns, and barriers to care between HIV-infected non-Hispanic blacks and whites in North Carolina.